Upaya Konservasi Pada Cagar Budaya Candi Tebing Gunung Kawi - I Made Krisnawan; Pande Komang Artika Antara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Gunung Kawi Cliff Temple is a temple complex located in the village of Tampaksiring, Gianyar, Bali, Indonesia. This temple complex is famous because it consists of stone monuments carved into the side of the Pakerisan river cliff. This temple is believed to have been built in the 11th century AD during the reign of King Anak Wungsu of the Udayana Kingdom. This temple complex consists of ten temples carved in relief on the cliff walls. Gunung Kawi Cliff Temple itself is divided into 3 temple locations, which include Group Five Temples, Group 4 Temples and Group 1 Temples. However, due to age, the original condition of Gunung Kawi Cliff Temple is getting more and more apprehensive. The entire temple has experienced weathering, even the carvings on some temples have begun to fade or become invisible. This study aims to explore the efforts that have been made to preserve the Gunung Kawi Temple Complex, with a focus on buildings or architecture in the Gunung Kawi Cliff Temple area. This study uses a qualitative approach by conducting interviews with members of the community who play a role in efforts to preserve the Mount Kawi Cliff Temple tourist attraction and field observations. The results of this study are that there are efforts that have been implemented for the preservation of the Gunung Kawi Cliff Temple Cultural Heritage by the community and also the Cultural Heritage Preservation Center. Gunung Kawi Cliff Temple Cultural Heritage Area. The conservation methods that are suitable to be applied to this Cultural Conservation object include cleaning, structural repairs, replacement of damaged materials, protection from environmental factors, routine maintenance.